Pilot optimization for OFDM in the RSSB system - Chen, Long; Yang, Ziteng; Yu, Qian (Frontiers in Physics, 2023)
To increase the receiving sensitivity of the reversely single-sideband (RSSB) system with orthogonal frequency division multiplexing (OFDM) signal transmission, we use the improved pilot interval scheme and pilot power scheme in this system. The improved pilot interval scheme uses more pilots in areas where channel conditions are relatively good to avoid signal–signal beat interference (SSBI) issues for sub-carriers. The improved pilot power scheme compensates for frequency-selective fading by increasing the pilot power in areas where channel conditions are relatively poor. According to the simulation, the generated 60 GHz optical millimeter wave with 2.5 G bandwidth OFDM signal is delivered over 100 km standard single-mode fiber (SSMF). The improved pilot interval scheme and pilot power scheme can increase the system’s receiving sensitivity by 2 dB, respectively. These schemes can enhance the system’s performance without increasing the complexity of the algorithm and the costs of the RSSB system.